2021
DOI: 10.1002/essoar.10506760.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tropospheric NO_2 and O_3 response to COVID-19 lockdown restrictions at the national and urban scales in Germany

Abstract: During the COVID-19 lockdown period, NO 2 concentrations decreased and O 3 concentrations increased in eight German cities • The degree of NO X saturation of ozone production is weakening from winter to summer • Meteorological variability adjusted by GEOS-Chem model simulations driven by the same emissions for 2020 and 2019

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Specifically, the emergence of COVID‐19 led to government restrictions on mobility, including shelter‐in‐place orders and bans on social events (World Health Organisation (WHO), 2020). There has been much interest in understanding and quantifying how these regulations modulated both emissions to the atmosphere and the chemical composition of the atmosphere (e.g., Balamurugan et al., 2021; Dietrich et al., 2021; Tanzer‐Gruener et al., 2020; Turner et al., 2020). Recent studies have tried to quantify the impact of the enforced and voluntary restriction of human activities (travel and work related) on global greenhouse gas (GHG) emissions (Forster et al., 2020; Le Quéré et al., 2020; Liu et al., 2020) and air pollution (e.g., Grange et al., 2020; Venter et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the emergence of COVID‐19 led to government restrictions on mobility, including shelter‐in‐place orders and bans on social events (World Health Organisation (WHO), 2020). There has been much interest in understanding and quantifying how these regulations modulated both emissions to the atmosphere and the chemical composition of the atmosphere (e.g., Balamurugan et al., 2021; Dietrich et al., 2021; Tanzer‐Gruener et al., 2020; Turner et al., 2020). Recent studies have tried to quantify the impact of the enforced and voluntary restriction of human activities (travel and work related) on global greenhouse gas (GHG) emissions (Forster et al., 2020; Le Quéré et al., 2020; Liu et al., 2020) and air pollution (e.g., Grange et al., 2020; Venter et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From March to June, the difference in solar zenith angle for Poland (latitude 49.00-55.04 °N, longitude 14.07-24.15 °E) is of only about 5 °-10 °, and as such, changes in solar zenith angle can be considered negligible for weather normalization over this domain, while for other studies they has to be considered, e.g., Balamurugan et al, 2021, Goldberg et al, 2020…”
Section: Meteorological Datamentioning
confidence: 99%
“…Several researchers used observations from space, in situ measurements, and models to analyse the impact of COVID-19 on NO 2 pollution. During the COVID-19 lockdown, there was a 6% decrease in NO 2 in Tehran, Iran (Sharifi and Felegari, 2022), 30%-39.79% drop in NO 2 in East China (Filonchyk et al, 2020;Fei et al, 2022), a 40%-50% drop in Arabian Pennisula (Karumuri et al, 2022), a 20%-40% reduction was recorded in India (Biswal et al, 2021), 9%-43% in the United States (Goldberg et al, 2020), 39% decrease in Greece (Koukouli et al, 2021), 23% drop was observed in Germany (Balamurugan et al, 2021), 50% reduction in Spain (Petetin et al, 2020), 67.7% drop in Rome, Italy (Bassani et al, 2021), and many more, especially those comparing the COVID-19 effect on NO 2 across more than one European country (e.g. Barré et al, 2021;Solberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%